Violence against children in early childhood: an analysis of the cases notified in the state of Pará-Brazil in the period from 2009 to 2019 (Research, Society and Development, 2021)
The present study aimed to analyze the characteristics of violence practiced against children in early childhood, notified by the health sector from January 2009 to July 2019 in the state of Pará-Brazil, based on a quantitative research, descriptive and exploratory. The results showed that female victimization (69.05%) was more reported than male (30.95%). Regarding race / color, black and brown children were more victimized (85.20%), both in relation to male and female victims. Violence occurred predominantly in the children's homes (86.26%). The type of violence that stood out was sexual violence (36.35%), followed by psychological-sexual violence (14.85%) and physical-psychological-sexual violence (14.19%). The victim's acquaintance represented the main aggressor (52.38%), followed by the father in relation to female children and the mother in relation to male children. The perpetrator of violence was predominantly male in relation to female victims (56.23%) and also predominant in relation to male victims (21.47%). It was possible to verify the prevalence of sexual violence associated with the female victim and the male author. The data suggest that an important percentage of children in early childhood in the state of Pará, are vulnerable to sexual violence, which can damage their development throughout the life cycle.